Nicorandil improves myocardial function by regulating plasma nitric oxide and endothelin-1 in coronary slow flow. Issue 2 (March 2015) - Chen, Zuoyuan; Chen, Xiuhua; Li, Shan; Huo, Xuezhen; Fu, Xiuxiu; Dong, Xiaonan
Abstract : Background: Coronary slow flow (CSF) is a special coronary microvascular disorder. The pathogenesis and effective therapeutics of CSF remain unclear. This study aimed to evaluate the global and regional functions of the left ventricle (LV) and investigate the efficacy of nicorandil in patients with CSF. Patients and methods: Thirty-six patients with CSF in the left anterior descending (LAD) branch and 20 patients with normal coronary arteries were included. Global and regional functions of the LV supplied by LAD were measured using conventional Doppler echocardiography and two-dimensional speckle tracking echocardiography, respectively, within 24 h after coronary angiography. Concentrations of plasma nitric oxide (NO) and endothelin-1 (ET-1) were detected using colorimetry and radioimmunoassay, respectively. The function of the LV and the levels of NO and ET-1 were also investigated before and 90 days after treatment with 15 mg/day of nicorandil. Results: Compared with the control group, the early diastolic peak velocity (E), E/A ratio, and plasma NO levels were lower, whereas the late diastolic peak flow velocity (A) and plasma ET-1 levels were significantly higher in the CSF group ( P <0.05). The longitudinal strain rate peak of the LV was reduced significantly in CSF patients ( P <0.001). After treatment, 75% (27/36) of CSF patients were free of chest pain. The values of E peak, E/A ratio, longitudinal strain rate peak, and plasma NO level were increased ( P <0.001), whereas the ET-1 level was decreased in CSF patients ( P <0.001). Conclusion: Nicorandil may improve chest pain symptoms and the impaired function of the LV, possibly by increasing plasma NO and reducing ET-1 in CSF.